Effects of the supply-side channel on stabilisation properties of policy rules - Jukka Railavo (Bank of Finland, 2003)
In this paper we introduce an application of the supply-side channel for fiscal policy to the basic New Keynesian model.We use a proportional tax rate instead of lump sum tax and introduce the distortions of a tax wedge.We derive a closed economy forward-looking model with government consumption and no capital. Households' labour supply decisions are endogenised.Monetary policy is conducted by a Taylor-type interest rate rule and fiscal policy follows a simple debt rule.We analyse the stability of the model when fiscal policy has both demand and supply-side effects and compare results with the standard case of only demand effects. We show that taking supply-side effects into account restricts the fiscal policy parameter range consistent with the dynamic stability of the economy.We also argue that allowing fiscal policy to affect both supply and demand results in more persistent inflation as well as output responses to shocks, than without the supply-side channel.We also discuss the different monetary and fiscal policy regimes and their implication on the stability of inflation and output.
URN:NBN:fi:bof-20140807250
Keywords: E52; E31; E63; 330; inflation; fiscal and monetary policy; stabilisation